واقع الخدمات التعليمية والصحية فى لواء المنتفق 1926 - 1928 : دراسة وثائقية - العيساوي، عبدالعال وحيد عبود (جامعة الكوفة - كلية التربية للبنات, 2014)
Education in Muntafig had become an inevitably social necessity for the development of life. It was characterized by simplicity going in line with the purposes and aims of the government to prepare administrative and technical cadres. Thus, the main interest was directed towards the spread of knowledge and stuffing students minds with all sorts of knowledge available at the time there in order to perform the goals behind the educational system. With regard to the health sector, plagues were a familiar phenomenon at that time. But, the government did all its best to provide the health requirement such as medical cadres and medicines. Health awareness has begun to gain priority over other things in Muntafig in order to end epidemics inherited from the time of the ottomans and the British.
Keywords: التعليم فى لواء المنتفق -- الخدمات الصحية فى لواء المنتفق -- العملية التربوية فى لواء المنتفق